ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN KREDIT PADA DEALER TOYOTA ASRI MOTOR PUCANG DI SURABAYA - Jhohana A. W. (PUTRA JAWA PUBLISHER, 2023)
Asri Motor is a trading company specializing in the sale of Toyota brand cars. Over time, Asri Motor has been designated as an official